INTONATION, RHYTHM AND OTHER POETRY FORM MAKING MEANS IN IMPLIED SENSE CREATION AND TRANSLATION - Kykot V. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with influence of intonation, rhythm, meter, sound and other poetry form means on implied sense creation and translation.